2010
DOI: 10.1111/j.1600-0714.2009.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Parotid sialosis: morphometrical analysis of the glandular parenchyme and stroma among diabetic and alcoholic patients

Abstract: These results indicate that the glandular hypertrophy in the diabetic parotid sialosis is not directly associated with the ductal and acinar size, amount of fatty tissue and ductal hyperplasy. Nevertheless, these findings show that the ductal dimensions and the proportion of adipose tissue are variables that allow us to establish histopathological differences between diabetic and alcoholic sialosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 8 publications
0
15
0
3
Order By: Relevance
“…Lilliu, M. Cossu, unpublished observation) nor by Merlo et al. in sialosis, where only changes in acinar size were found . On the other hand, experiments on rats with induced diabetes showed that submandibular gland morphology is more strongly affected by the diabetic status, even when glycemic level was controlled .…”
Section: Discussionmentioning
confidence: 87%
“…Lilliu, M. Cossu, unpublished observation) nor by Merlo et al. in sialosis, where only changes in acinar size were found . On the other hand, experiments on rats with induced diabetes showed that submandibular gland morphology is more strongly affected by the diabetic status, even when glycemic level was controlled .…”
Section: Discussionmentioning
confidence: 87%
“…Our observations substantiate literature data only partially, because reports on salivary glands in controlled diabetes are rather scarce, often contradictory, and chiefly based on chemical analysis of saliva (Fisher et al, ; Dodds and Dodds, ; Chavez et al, ; Bernardi et al, ; Barnes et al, ). From a morphological point of view, severe alterations in human salivary glands were described as effects of diabetes, but nearly all reports concerned cases of evident sialosis (Donath and Seifert, ; Islas Andrade et al, ; Satoh and Yoshihara, ; Merlo et al, ). Many morphological alterations in salivary glands were also described in rodents (Cutler et al, ; Hand and Weiss ; Reuterving et al, ; Anderson et al, ; Szczepanski et al, ), in which the effects of this disease were found to be attenuated but not abolished by insulin treatment (Chan et al, ; Caldeira et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sialosis of both etiologies is accompanied by xerostomia, or a sensation of dry mouth, with a decrease in the salivary flow. 23 Histopathologic reports typically reveal a fatty infiltration of parenchyme with a decrease in the number of the acini structures and acinar hypertrophy. 23 On a CT scan, a normal gland shows multiple irregular areas of hypodensity, reflecting the gland's fatty content.…”
Section: Immunoglobulin G4-related Diseasementioning
confidence: 99%
“…23 Histopathologic reports typically reveal a fatty infiltration of parenchyme with a decrease in the number of the acini structures and acinar hypertrophy. 23 On a CT scan, a normal gland shows multiple irregular areas of hypodensity, reflecting the gland's fatty content. For patients with alcoholic sialosis, clinicians must direct treatment at the dire aspect of the problem-liver damage.…”
Section: Immunoglobulin G4-related Diseasementioning
confidence: 99%